The Relationship Between Cervical Cancer Severity and miRNA-205 Expression in Bali - Kartika Sari; Desak Putu Oki Lestari; Novitasari Novitasari; Yudhi Nugraha; Vivitri Dewi Prasasty; Septi Panca Sakti (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2022)
Cervical cancer is the one of leading cause of death for women worldwide. It occurs due to infection with the human papilloma virus (HPV) which attacks the cervix in the female reproductive organs. The detecting cervical cancer method is by using pap smears and liquid based cytology (LBC) and vaccinations. However, both methods are limited in detecting cervical cancer quickly and accurately. This study aims to find potential biomarkers that will be used to quickly detect the development of cervical cancer. Large-scale studies have shown that microRNA-205 (miRNA) regulation has a very important role in various types of cancer including cervical cancer. The extraction and synthesis of cDNA from 26 preparations of cervical cancer paraffin blocks were measured by quantitative real time PCR to evaluate the expression of miRNA-205 as a biomarker of cervical cancer in cervical cancer samples. Statistical results showed that there was a significant difference in the expression of miRNA-205 which was relatively higher in cervical cancer patients (p<0.05) miRNA-205. In addition, the increased expression of miRNA-205 is associated with an increase in the severity of cervical cancer. We conclude that miRNA-205 is a potential candidate for cervical cancer molecular biomarker.